Pakistan : Second Review and Request for the Augmentation of Access Under the Stand-By Arrangement; Staff Report; Staff Supplement; Staff Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Pakistan. (IMF Staff Country Reports; Country Report ;, 2009)
This paper discusses key findings of the Second Review for Pakistan and a request for the augmentation of access under the Stand-By Arrangement. Program performance has been mixed. All end-March quantitative performance criteria were met, but structural reform has been slower than programmed. The authorities indicated that the fiscal deficit ceiling may have been exceeded by 0.9 percent of GDP and, therefore, request a waiver of nonobservance for the related end-June 2009 performance criterion. The authorities also request waivers of applicability for other end-June quantitative performance criteria.